Modification of Breast Stroke Leg Movement Exercises in Extracurricular Swimming Courses at Yos Sudarso Junior High School (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effectiveness of breaststroke leg movement training modifications in improving swimming skills of extracurricular swimming participants at SMP Yos Sudarso. The background of this study is based on the low mastery of basic leg movement techniques in breaststroke which is one of the inhibiting factors in student achievement. The research method used is a quantitative approach with a quasi-experimental design. The subjects of the study were 20 students participating in extracurricular swimming who were selected purposively. The instrument used was an observation sheet for breaststroke leg movement technique skills. The results of the study showed that the application of training modifications, such as the use of a buoy board and variations in movements on land, significantly improved the quality and coordination of students' leg movements. Thus, training modifications have proven effective and can be used as an alternative learning approach that is fun and adaptive for beginner students in extracurricular swimming activities.